2018
DOI: 10.3390/ma12010043
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Induced Electrocatalysis with Multi-Component Nanostructures

Abstract: Noble metal nanostructures are exceptional light absorbing systems, in which electron–hole pairs can be formed and used as “hot” charge carriers for catalytic applications. The main goal of the emerging field of plasmon-induced catalysis is to design a novel way of finely tuning the activity and selectivity of heterogeneous catalysts. The designed strategies for the preparation of plasmonic nanomaterials for catalytic systems are highly crucial to achieve improvement in the performance of targeted catalytic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Mechanism pathways of LSPR can be classified into 2 major groups: Radiative‐nonradiative decays and direct‐indirect mechanisms. The radiative decay ( Figure 2a ) , upon which the plasmon decays into photons resulting in strong light‐scattering effects, [29] enables the intramolecular excitation of molecules. The energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) matches the energy of the re‐emissive photons from plasmonic materials [30] .…”
Section: Fundamentals On Lsprmentioning
confidence: 99%
“…Mechanism pathways of LSPR can be classified into 2 major groups: Radiative‐nonradiative decays and direct‐indirect mechanisms. The radiative decay ( Figure 2a ) , upon which the plasmon decays into photons resulting in strong light‐scattering effects, [29] enables the intramolecular excitation of molecules. The energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) matches the energy of the re‐emissive photons from plasmonic materials [30] .…”
Section: Fundamentals On Lsprmentioning
confidence: 99%
“…In the second and last part, the discussed topics are devoted to chemistry and sensing, such as surface-enhanced fluorescence, surface-enhanced Raman scattering (SERS), sum-frequency generation (SFG) spectroscopy, and electrocatalysis by using plasmonics [34,35,36,37,38,39,40]. Concerning the surface-enhanced fluorescence, Lu et al numerically demonstrated a high enhancement effect of the fluorescence signal obtained with a hybrid metal-dielectric nano-aperture antenna consisting of silicon and gold layers [34].…”
Section: Synopsismentioning
confidence: 99%
“…To conclude this part, as well as this special issue dedicated to “ Plasmonics and its Applications ”, Subramanian et al presented a review on the electrocatalysis induced by plasmon with multi-component nanostructures. Indeed, the authors highlight the recent progress obtained in the synthesis of these multi-component nanostructures, especially for the plasmonic electrocatalysis of major fuel-forming and fuel cell reactions [40].…”
Section: Synopsismentioning
confidence: 99%
“…Thus, if we could develop more tunable wet chemical methods that do not involve templating and are free of Pt and/or Pd, it would facilitate the design of new, more efficient and sustainable electrocatalysts. Nanostructures based on AuAg alloys in particular have not only very strong plasmonic characteristics, but also possess interesting electrocatalytic properties [41]. This was recently highlighted by Xu et al [42], who showed that the white light irradiation of AuAg nanobowls results in amplifying their performance for EGOR.…”
Section: Introductionmentioning
confidence: 98%